The turkey : an American story - Smith, Andrew F., 1946- (Food series., 2006)
Fondly remembered as the centerpiece of family Thanksgiving reunions, the turkey is a cultural symbol as well as a multi-billion dollar industry. As a bird, dinner, commodity, and national icon, the turkey has become as American as the bald eagle (with which it actually competed for supremacy on national insignias)._x000B__x000B_Food historian Andrew F. Smith's sweeping and multifaceted history of Meleagris gallopavo separates fact from fiction, serving as both a solid historical reference and a fascinating general read. With his characteristic wit and insatiable curiosity, Smith presents the turkey in ten courses, beginning with the bird itself (actually several different species of turkey) flying through the wild. The Turkey subsequently includes discussions of practically every aspect of the iconic bird, including the wild turkey in early America, how it came to be called "turkey," domestication, turkey mating habits, expansion into Europe, stuffing, conditions in modern industrial turkey factories, its surprising commercial history of boom and bust, and its eventual ascension to holiday mainstay. The second half of the book collects an amazing array of over one hundred historical and modern turkey recipes from across America and Europe. Historians will enjoy a look back at the varied appetites of their ancestors, and seasoned cooks will have an opportunity to reintroduce a familiar food in forgotten ways._x000B_